PENERAPAN IPTEK PADA USAHA KUE KERING DESA BUGO KABUPATEN JEPARA - Setiati, Ning; Bintari, Siti Harnina; Christijanti, Wulan (Universitas Negeri Semarang, 2015)
Objectives to be achieved in service activities is to foster the spirit of starting a new life for the 5 farmers who suffered catastrophic cold lava flood particular group Livestock quail Tani Mulyo Hamlet Quick Village Gondosuli Muntilan district and 5 breeders are joined in Group Livestock quail Rejeki Hamlet Macanan Banyudono Shaman District. Specific targets are the seeds quail ready to lay that out of 1,000 head of targeted quail egg can produce 75%, assuming a quail egg-laying 1 egg / day, sold at a retail price of Rp. 210, - / point. Results of these activities are still limited availability of seedling 3,690 tails with an average weight increase in the age of 2 weeks 28 grams and 3,450 head at the age of 8 weeks to 167 grams. Egg production reached 86% before the arranged marriage which only reached 66% egg production quail. To foster the spirit of entrepreneurship that is able to think of creative and innovative and able to read the opportunities as well as clever use it in accordance with the capabilities and not focused on just one type of work just the wives of farmers tried to create diversified products made from meat and quail eggs.